Lastnosti bolnikov z mielodisplastičnim sindromom in njihova obravnava na kliničnem oddelku za hematologijo, UKC Ljubljana, v obdobju 2008-2012 - Sever, Matjaž (Zdravniški vestnik, 2012)
Background: Myelodysplastic syndromes (MDS) are a group of clonal diseases classified by the World Health Organisation (WHO) as refractory anemia (RA), refractory anemia with ringed syderoblasts (RARS), refractory cytopenia with multilineage displasia (RCMD), refractory anemia with excess blasts (RAEB) type 1 and 2, MDS unclassified and MDS with del 5q. Bone marrow aspiration andcytogenetics are most important for diagnosis. Patients are classified intoprognostic groups according to the International prognostic scoring system(IPSS). Therapy is started according to clinical presentation and prognosis. Patients are treated with transfusions, growth factors, azacytidine, conventional chemotherapy or bone marrow transplant. Methods: Institutional database was searched for MDS patients diagnosed in the period between 2008-2012 at the Department of Hematology, University Medical Centre Ljubljana. We classified them according to WHO and IPSS. Descriptive statistics with survival curves were performed. Results: We identified 111 patients with MDS, median age 74.6 years (14.4-91.3). According to WHO, they had RA n = 24, RARS n = 1, RCMD n = 40, RAEB-1 n = 17, RAEB-2 n = 18, MDS unclassified n = 3, and del(5q) syndrome n = 2. There were no statistical differences in the survival according to diagnosis. We performed cytogenetics in 43 patients, in 19 within three months from referral. Patients were classified according to IPSS as low risk n = 4, intermediate- 1 n = 6, intermediate-2 n = 6 and high risk n = 3. Patients with low and int-1 risk hadlonger survival (p = 0.0167). During the follow-up of 1.5 years (0.38-9.1),58 patients were treated with transfusions or epoetins, 21 patientswith chemotherapy and 6 with immunosupressive therapy. Eleven patientshad transformation of MDS. Forty-three patients were lost to follow-upand 10 patients died. Conclusions: MDS is a rare disease. At presentation, a complete diagnostic workup should be performed. Patients with low or intermediate-1 risk have longer survival.
Keywords: bolniki; diagnosis; diagnostika; mielodisplastični sindrom; myelodisplastic syndrome; patients characteristic; therapy; zdravljenje